Variety of Antibody Responses to BNT162b2 and BBIBP-CorV Vaccinations Against COVID-19 Infections in Baghdad and Fallujah, Iraq - Mohammed A. Hamad; Mohammed N. Abed; Najemaddin A. Hamad; Mariam A. Abdul-Latif; Nehal A. Mohammed; Aya N. Abdul-Razaq; Rawaa A. Muhammed (UKH Journal of Science and Engineering, 2023)
The huge impact of COVID-19 worldwide led to the rapid development of vaccines with inadequate data about its longevity, effectivity, and safety. This study aims to evaluate the effectiveness and safety of COVID-19 vaccines available in Iraq and to measure longevity of created antibody response among different time points of both Pfizer-BioNTech and Sinopharm vaccines in Baghdad and Fallujah, Iraq.